Application of Soil Structure Interaction on Building with Basement using Nonlinear Soil Springs - Anastasia Jesica; Pamuda Pudjisuryadi; Dario Rosidi (Civil Engineering Dimension, 2023)
In a typical building design, the interaction between building and surrounding soils is often ignored. Since soil is deformable and has limited capacity to resist loads, this interaction, called soil-structure interaction (SSI), could alter building responses, especially during earthquake loadings for buildings with significant basement depths. In this study, a 10-story reinforced concrete building with 3-level basement was used to evaluate the effects of SSI on building during earthquakes. Dynamic time response analyses were performed using earthquake time histories scaled to a design response spectrum for a Surabaya, Indonesia, location. Soil responses during earthquakes were modeled using nonlinear hysteresis normal and elastic-perfectly plastic frictional soil springs, developed using the hardening soil with small strain stiffness model. Depth-varying ground motions were also applied along the basement depth. The results show inconclusive SSI effects, where some of the time histories produce greater base shears and inter-story drifts when SSI is considered, while others show the opposite results.